Requirement gathering using five whys and drill downs techniques for development of agent property system for the licensed auctioneer company / Nur Farahin Nadia Yusni - Yusni, Nur Farahin Nadia (2017)
The stakeholder for this project is Licensed Auctioneer Company that are located at Batu Pahat, Johor. Currently, they are using the manual system which they keep all the data in files and advertise their property through newspaper. The company are covering the auction around Johor. They are facing the problem of unmanageable data, uncertainty of the stakeholder relating to requirement and lastly the inefficient medium of advertising that required high cost. The solution for the unmanageable data problem is by developing the APS that can manage all the data for the auction process. The system is for the staff to manage the staff, lawyer, buyer, client and property and also for public to survey the auction property based on area and type of property. There are three objectives for this project which are to gather and analyze requirements using chosen techniques, design and develop the APS. The method used was waterfall model that have four phases which are knowledge acquisition, requirement analysis, system design and implementation phase. Each phase has their own activities and deliverable that helps in achieving their objectives and lastly completing the project. The project only focus on the auction property around Johor. The finding of this project is to apply the solution that are being retrieved by using those techniques to Agent Property System that can help both actors, staff and also public in performing their business. For public, the system are for them to do auction property survey only. Lastly, the system are recommend to provide the online auction for the public that having a time constraint in the future.